Metabolic profiling and antimicrobial activity of Bistorta amplexicaulis D. don by in-vitro implicated through computational studies - Javid, Hanan; Yousuf, Umar; Ul Qadir, Roof; Magray, Junaid A.; Wani, Bilal A.; Islam, Tajamul; Nawchoo, Irshad A.; Gulzar, Shabana (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceBistorta amplexicaulis is an important medicinal plant from the Polygonaceae family. It is been utilized traditionally to cure several ailments. However, its essential bioactivities and antimicrobial mechanisms have remained unexplored.Aim of the studyThe present study aimed to investigate the antimicrobial mechanisms of various extracts of B. amplexicaulis through the application of standard antimicrobial assays. We investigated by molecular dynamics (MD) simulation studies, the possible targets of one of the compounds found in this plant.Materials and methodsThe qualitative and quantitative analysis of phytochemicals was performed using established methodologies. Additionally, high-resolution liquid chromatography-mass spectrometry (HR/LC-MS) analysis was carried out on the active extracts to identify the secondary metabolites present in various parts of B. amplexicaulis. Moreover, using in vitro methods, these extracts have been tested for antimicrobial activity against a variety of bacterial (Bacillus subtilus, Staphylococcus aureus, Proteus vulgaris, Escherichia coli) and fungal (Aspergillus flavus, Aspergillus niger, Penicillium notatum) strains. Besides, molecular modeling of identified compounds was conducted against various crucial microbial drug target proteins.ResultsMetabolic profiling demonstrates that around 22 and 35 bioactive compounds are identified from the belowground and the aboveground parts, respectively, and many of these compounds have therapeutic uses. Further, ethyl acetate extracts from the underground parts showed the widest Inhibition Zone Diameter (IZD) at 18.07 ± 0.38 mm against B. subtilus at 1,000 μg/mL, and the smallest IZD was shown by methanolic extracts of aboveground parts against P. vulgaris (5.50 ± 0.39 mm). The inhibitory activity of various doses of plant extracts against A. niger, A. flavus, and Penicillium notatum was also tested. At a concentration of 600 μg/mL, ethyl acetate extracts from the underground parts exhibited the most significant inhibition against Penicillium notatum, leading to an 84.56% ± 2.56% reduction in mycelial growth compared to the control. In contrast, the lowest inhibition was observed in methanol extracts from the aboveground parts against A. flavus, resulting in a 26.18% ± 2.58% inhibition in mycelial growth. In addition, molecular docking and MD simulation studies on the compounds revealed significant binding affinity, supporting the observed in-vitro antimicrobial activity.ConclusionOverall, this study offers an extensive understanding of the chemical composition of B. amplexicaulis extracts and their antimicrobial potential. Furthermore, Computational studies have provided deep insights into how plant secondary metabolites interact with microbial drug target proteins, leading to more targeted and effective antimicrobial therapies.